ALGORITHM TRANSPARENCY AS A SINE QUA NON PREREQUISITE FOR A SUSTAINABLE COMPETITION IN A DIGITAL MARKET? (EU and comparative law issues and challenges series (ECLIC), 2021)
Algorithms play a fundamental role in the digital economy. Their impact on the situation of market participants is significant. Hence, ensuring transparency of algorithms, through access to them, is crucial for the proper functioning of the market. Several models of algorithmic transparency are analyzed in the paper: from lack of transparency to complete regulation of algorithms. In particular, transparency through explanation, and “on-demand transparency” were proposed. The goal of the paper is to determine the optimal form and scope of regulation of this area, in order to ensure sustainable competition in the digital market. Hence, the paper focuses on the concept of algorithmic transparency, the nature of the competition in the digital market, the role of algorithms within the digital trade, and problems related to the regulation of algorithms. This allows to answering the question of whether algorithmic transparency is an indispensable condition for sustainable competition in the digital market, and what are the legal challenges, which may arise with respect to various models of algorithm transparency. The paper  is embedded  within the EU legal framework, discusses new legislative developments in the EU law, such as the proposal for the Digital Markets Act, and includes analysis of EU antitrust case-law and market practices.